1994
DOI: 10.1128/aem.60.4.1353-1358.1994
|View full text |Cite
|
Sign up to set email alerts
|

A reporter gene construct for studying the regulation of manganese peroxidase gene expression

Abstract: The orotidylate decarboxylase (ODase) gene (ural) from Schizophyllum commune was utilized as a reporter for studying Mn regulation of the manganese peroxidase (MnP) gene (mnp) from the lignin-degrading basidiomycete Phanerochaete chrysosporium. A 1,500-bp fragment of the mnpl promoter was fused upstream of the coding region of the ODase gene in a plasmid (pAMO) containing the S. commune adeS gene as a selectable marker. pAMO was used to transform a P. chrysosporium adel urall mutant lacking endogenous ODase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The MnP activity reached a maximum level after 60 h and decreased thereafter. No new activity peak appeared on day 5 or 6 in any of the cultures; this is the period during which endogenous MnP is expressed in low-nitrogen cultures (5,11). These observations indicated that the activity observed in the transformants was due to rMnP.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The MnP activity reached a maximum level after 60 h and decreased thereafter. No new activity peak appeared on day 5 or 6 in any of the cultures; this is the period during which endogenous MnP is expressed in low-nitrogen cultures (5,11). These observations indicated that the activity observed in the transformants was due to rMnP.…”
Section: Resultsmentioning
confidence: 88%
“…MnP is a component of the lignin degradation systems of most, if not all, white rot fungi (19,32,35), including P. chrysosporium, in which it is expressed during idiophasic growth (10,11,14,38). MnP is a unique peroxidase in that its primary substrate is Mn(II), which is oxidized to Mn(III), and MnP activity is stimulated by various organic acid chelators, especially oxalate, which is secreted by P. chrysosporium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…© 1998 The Society for Applied Microbiology have been used for gene replacement ) and for production of recombinant manganese peroxidase in P. chrysosporium (Mayfield et al 1994). In addition, they have been employed to develop a reporter gene construct for studying the regulation of mnp1 gene expression (Godfrey et al 1994). However, it would be useful to have systems that do not depend on the presence of a particular auxotrophic marker, and that are non-integrative.…”
Section: Introductionmentioning
confidence: 99%